Mechanisms of blaIMP-4 dissemination across diverse carbapenem-resistant clinical isolates - Ying Fu; Faye C. Morris; Stephanie C. Pereira; Xenia Kostoulias; Yan Jiang; Callum Vidor; Galain Williams; Yogi Srikhanta; Nenad Macesic; Yunsong Yu; Dena Lyras; Anton Y. Peleg (Journal of Global Antimicrobial Resistance)
ABSTRACT: Objective: The IMP-4 carbapenemase is an endemic cause of carbapenem resistance in the Asia-Pacific region. Our aim was to determine the dissemination mechanism of the blaIMP-4 gene. Methods: Twelve representative Australian IMP-4 clinical isolates from The Alfred Hospital (Victoria, Australia) were characterised using antimicrobial susceptibility testing, with their genome and plasmid assemblies analysed. The conjugation efficiencies of different plasmids were investigated using filter mating with four recipient strains across two species. Results: Selected IMP-4 isolates included six species and four genera (Enterobacter, Klebsiella, Serratia, and Acinetobacter), whereby isolates of the same species belonged to the same sequence type and were closely related. Four IMP-4 plasmid types were noted: IncHI2A types 1 and 2 (Klebsiella spp. and Enterobacter hormaechei, respectively), IncC (Serratia marcescens and Klebsiella pneumoniae), and a novel type in Acinetobacter pittii. Sequence homology was observed across all plasmids at the blaIMP-4 location, termed Region I, with IS26 on IncHI2A, and IS5075 and Tn3 resistance gene cassettes present on IncC plasmids. Genomic rearrangements mediated by IS26 or Tn3 and IS5075 were identified in Region I of plasmids from the same Inc type. The plasmids of each Inc type were capable of conjugative transfer with varying efficiency. IncH12A plasmids and K. pneumoniae IncC displayed higher transfer efficiencies than other plasmids examined in this study when using the recipient E. coli strain J53 (with conjugation efficiencies of 1.17×10−2 to 5.02×10−5, P < 0.001). Conclusions: Clonal spread, Inc type, homologous region, and insertion sequences are important mobility factors in the dissemination and evolution of blaIMP-4 plasmids.